Alex Rider : Nightshade Revenge - Book 14 - Horowitz, Anthony, 1955- (New York : Philomel, 2024)
When Nightshade kidnaps his best friend, teen spy Alex Rider must enter the world of virtual reality gaming where the lines between what's real and what's digital are deliberately being blurred by a ruthless enemy.
The invisible bullet -- Separate ways -- Flips and ollies -- Decision time -- Getting in -- Getting out -- Execution -- Pushback -- Explanations -- Old friends -- Big Bessie -- Ten seconds -- The tiger -- Mission Bay -- Inside information -- The church -- The arena -- The blue devil -- Game over -- El Dorado -- Nightfall -- Shoot-out -- Resignation.
Keywords: Rider, Alex -- (Fictitious character) -- Juvenile fiction; Kidnapping -- Juvenile fiction; Virtual reality -- Juvenile fiction; Video games -- Juvenile fiction; Friendship -- Juvenile fiction; Spies -- Fiction; Kidnapping -- Fiction; Virtual reality -- Fiction; Video games -- Fiction; Adventure and adventurers -- Fiction; Young adult fiction; Action and adventure fiction; Spy stories; Thrillers (Fiction); Young adult fiction; Action and adventure fiction; Spy fiction; Thrillers (Fiction); Novels; Romans